Developing GLOSABIO: A Mobile Learning Application to Enhance Scientific Terminology Mastery - Annisa Puji Astuti; Deni Parlindungan; Silvia Syeptiani; Arsela Eko Listiono; Nanik Nanik; Amaira Utami; Zico Fakhrur Rozi (Equator Science Journal, 2026)
Mastery of biological scientific terms often poses a challenge for students in General Biology courses. This study aimed to develop GLOSABIO, an Android-based learning application designed to improve students’ understanding of biological scientific terminology. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included 33 students from the Science Education Study Program at the University of Bengkulu. Product validation was conducted by material and media experts using validation sheets, while student response questionnaires and a 33-item matching test were used to measure practicality and effectiveness. Data were analyzed using descriptive quantitative analysis, percentage analysis, and N-Gain analysis. The validation results showed that GLOSABIO was highly valid (93%), while practicality testing indicated that the application was very practical (89%). Students’ average scores increased from 51.97 in the pretest to 86.41 in the posttest, with an N-Gain score of 0.717 categorized as high/effective. The paired sample t-test showed a significant difference between pretest and posttest scores (p < .001), with a very large effect size (Cohen’s d = 2.45). These findings demonstrate that GLOSABIO is valid, practical, and effective in enhancing students’ mastery of biological scientific terminology.